Capturing experiences artistic self-expression with surrealist documentary photography using figital photography - Sanchez, Samuelle Marionne C.
This artistic practice study explores the possibility of using Surrealist principles in contemporary documentary photography. It is phenomenological in nature, inspired from an earlier photo project which featured the municipality of New Bataan, Compostela Valley weeks after it was devastated by the typhoon Bopha, locally known as Pablo. The study discussed how Surrealism and documentary photography were used by documentary photographers in their practice, by examining their photographs and written literature. Using these discussions as background, the form, materials, and context of artistic practice for this study was identified using theories of gestalt and cognitive perception. The photographs were captured on two occasions, exactly a year apart from each other. The figital photography was used to create photographs and to translate the experiences they acquired from the subject and photographer into the final print. After careful selection and post-processing, they were shown in a photo exhibit on two occasions. This study shows how an artist applies the visual language of any artistic movement in communication art. In addition, it has also defined the visual signature and genre of the author, giving him the opportunity to establish himself as a photographer who shoots experiences not megapixels.
Thesis (B.A. Communication Arts) -- University of the Philippines Mindanao
Keywords: Communication Arts -- Media Arts